Preferred prenatal counselling at the limits of viability: a survey among Dutch perinatal professionals - R. Geurtzen; Arno Van Heijst; Rosella Hermens; Hubertina Scheepers; Mallory Woiski; Jos Draaisma; Marije Hogeveen (BMC, 2018)
Abstract Background Since 2010, intensive care can be offered in the Netherlands at 24+0 weeks gestation (with parental consent) but the Dutch guideline lacks recommendations on organization, content and preferred decision-making of the counselling. Our aim is to explore preferred prenatal counselling at the limits of viability by Dutch perinatal professionals and compare this to current care. Methods Online nationwide survey as part of the PreCo study (2013) amongst obstetricians and neonatologists in all Dutch level III perinatal care centers (n = 205).The survey regarded prenatal counselling at the limits of viability and focused on the domains of organization, content and decision-making in both current and preferred practice. Results One hundred twenty-two surveys were returned out of 205 eligible professionals (response rate 60%). Organization-wise: more than 80% of all professionals preferred (but currently missed) having protocols for several aspects of counselling, joint counselling by both neonatologist and obstetrician, and the use of supportive materials. Most professionals preferred using national or local data (70%) on outcome statistics for the counselling content, in contrast to the international statistics currently used (74%). Current decisions on initiation care were mostly made together (in 99% parents and doctor). This shared decision model was preferred by 95% of the professionals. Conclusions Dutch perinatal professionals would prefer more protocolized counselling, joint counselling, supportive material and local outcome statistics. Further studies on both barriers to perform adequate counselling, as well as on Dutch outcome statistics and parents' opinions are needed in order to develop a national framework. Trial registration Clinicaltrials.gov, NCT02782650, retrospectively registered May 2016.